Development of functional ice cream using basil oil microcapsules - Paul, Veena; ., Arvind; Rai, Dinesh Chandra; Pandhi, Shikha; Seth, Ankit (Indian Journal of Dairy Science, 2020)
The frozen dairy products like ice cream act as vehicles for incorporating natural-bioactive ingredients to provide various nutritional health benefits. Basil is valued for its medicinal and therapeutic properties. In the present study, basil oil microcapsules were incorporated in ice cream. Ice cream mix with 10% milk fat, 12% sucrose, 0.5% stabilizer, and 0.5 % emulsifier was prepared. Basil oil was encapsulated by spray drying in 1:2 (core to coating ratio) using sodium alginate and maltodextrin as wall material. Basil oil microcapsules were incorporated at 0.5% w/v of ice cream mix. After experimentation, it was found that the sensorial attributes of ice cream incorporated with basil oil microcapsules were slightly lower than the control ice cream. The basil oil microcapsules brought considerable variations in overrun and hardness of ice cream. Furthermore, the ice cream incorporated with basil oil microcapsules shows high antioxidant (94.57±0.06% DPPH inhibition) and phenolic content (76.80±0.11 µg GAE/ml) as compared to ice cream incorporated with basil oil (93.54±0.13% DPPH inhibition and 58.35±0.17 µg GAE/ml total phenolic content).